Optimizing Social Media to Enhance a Positive Image in Junior High Schools - Ajeng Tanjiah Setia Mukti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This research is motivated by the conditions at SMP Negeri 2 Kalipucang, where social media has begun to be used as a means of communication but has not yet been managed optimally. School social media accounts, such as Instagram and TikTok, have so far only been used to document activities, without mature content planning. Therefore, this study aims to explore how the optimization of social media plays a role in shaping a positive image for the school.This research uses a qualitative method with a case study approach. Data collection techniques were carried out through semi-structured interviews with the principal, public relations officer, social media admin, teachers, students, and parents. Additionally, the researcher also observed the school's social media activities. However, its management is still conducted in a simple manner and has not involved a dedicated team. The school does not yet have narrative guidelines, a content calendar, or a clear communication strategy.